The effect of surface roughness on the transfer of polymer films under unlubricated testing conditions (2015)
Blended Polyetheretherketone (PEEK) and polyimide-based polymers are excellent lighter tribomaterials that make possible the replacement of sliding metallic components in machinery. In this work a quantitative analysis of the effect of surface roughness on the transfer of polymer films was investigated using a specialized tribometer, under air-conditioning and refrigeration specific operating conditions. Specifically, polyimide (Vespel SP-21), polyimide (Vespel SP-211), PEEK with carbon fibers, and Aromatic Thermosetting Polyester (ATSP) polymer pins were tested against gray cast iron disks under unlubricated unidirectional conditions. It was found that a continuous transfer layer of polymer on the surface of the cast iron disks with mirror finish (low surface roughness) was produced in all the combinations of tested blended polymers. In the case of the polymer pins tested against cast iron disks with high surface roughness, a discontinuous transfer layer was observed